2023
DOI: 10.3389/fmicb.2023.1233555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of symbiotic fungi-Armillaria gallica on the yield of Gastrodia elata Bl. and insight into the response of soil microbial community

Yanhong Wang,
Jiao Xu,
Qingsong Yuan
et al.

Abstract: Armillaria members play important roles in the nutrient supply and growth modulation of Gastrodia elata Bl., and they will undergo severe competition with native soil organisms before colonization and become symbiotic with G. elata. Unraveling the response of soil microbial organisms to symbiotic fungi will open up new avenues to illustrate the biological mechanisms driving G. elata’s benefit from Armillaria. For this purpose, Armillaria strains from four main G. elata production areas in China were collected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Mortierella rishikesha maintained highest relative abundance (>9%) in the rhizosphere throughout the growth stages of G. elata , indicating that it might be a core fungal species under greenhouse conditions. A high relative abundance of Mortierella has also been observed in the fungal communities of G. elata by Wang et al (2023) and Yu et al (2023) . Mortierella species in agricultural soils, the rhizosphere, and vegetable tissues are plant growth-promoting fungi ( Ozimek and Hanaka, 2020 ).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Mortierella rishikesha maintained highest relative abundance (>9%) in the rhizosphere throughout the growth stages of G. elata , indicating that it might be a core fungal species under greenhouse conditions. A high relative abundance of Mortierella has also been observed in the fungal communities of G. elata by Wang et al (2023) and Yu et al (2023) . Mortierella species in agricultural soils, the rhizosphere, and vegetable tissues are plant growth-promoting fungi ( Ozimek and Hanaka, 2020 ).…”
Section: Discussionmentioning
confidence: 81%
“…TE significantly inhibited the growth of fungal strains, such as C. novozelandicum, B. cinerea , and P. digitatum , which is consistent with the decline in the relative abundance of the Chaetomium and Penicillium genera and the absence of Botrytis genus in the rhizosphere. Several previous studies have reported that the bacterial and fungal communities in the cultivated soil of G. elata were significantly altered by Armillaria strains ( Collins et al, 2013 ; Wang et al, 2023 ) and Mycena strains ( Yu et al, 2023 ). Armillaria mellea produces many antibacterial and antifungal compounds, such as sesquiterpene aryl esters and armillaric acid, which exhibit high inhibitory activity against Gram-positive bacteria, yeast, Streptococcus spp., Mucor spp., Trichoderma spp., Rhizopus stolonifer, Fusarium spp., and Gliocladium viren ( Richard, 1971 ; Obuchi et al, 1990 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation